Elective Oocyte Cryopreservation - Saeideh Dashti; Maryam Eftekhar (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: In recent years, techniques for oocyte cryopreservation have aided in preserving women's fertility. Initially, oocyte cryopreservation was implemented for females with diminished ovarian reserves. This approach is appropriate for women who are at risk of diminished ovarian reserves, including those undergoing chemotherapy, radiotherapy, or other conditions impacting ovarian reserve. It provides them the opportunity to have biological children later on.  As more women choose to delay pregnancy and face declining ovarian reserves with age, oocyte cryopreservation has been made available to healthy women. Research did not demonstrate any difference in fertilization and pregnancy rates between fresh and frozen-thawed oocytes. Assessing ovarian reserve is essential prior to this procedure. Anti-Müllerian hormone levels and antral follicle counts are regarded as the most accurate indicators for forecasting ovarian response. Age is recognized as the key factor influencing oocyte quality and success rate. There is no agreement on the optimal age and quantity of oocytes for oocyte cryopreservation. Certain researchers have suggested an age limit of less than 35 years. Each additional frozen oocyte holds significance. Having 25 oocytes is linked to a 95% cumulative live birth rate in women under 35 years old. Conclusion: Elective oocyte cryopreservation provides an opportunity for women to preserve their fertility in future. Cryopreserved oocyte can lead to decreased risk of oocyte donation in the future and allows women to have their own genetic child. It is important that providers ensure that these women are informed about efficacy, safety and help them to make the best decisions. Some researchers have recommended an age below 35 years.